Cytotoxicity assessment of cultivable marine cyanobacterial extracts in Artemia salina (brine shrimp) larvae and cancer cell lines. (February 2013) - Maruthanayagam, V.; Nagarajan, M.; Sundararaman, M.
Abstract In this study, we investigated the cytotoxicity of marine cyanobacterial organic extracts against Artemia salina and different human cancer cell lines. The extract of Geitlerinema sp. CNP 1019 showed very high toxicity to brine shrimp at LC50, 32 μg mL−1. Furthermore, the extract was screened for cytotoxic activity against HT-29 (colon), HeLa (cervix), MCF7 (breast), KB (oral) and Hop2 (lung) cancer cell lines. It showed specific cytotoxicity against MCF7 with the GI50 (growth inhibition) value of 25.7 μg mL−1. Furthermore, the crude extract was fractionated by column chromatography. The active fraction was identified by brine shrimp toxicity assay, analyzed by high performance thin layer chromatography and gas chromatography–mass spectrometry.